Group identity modulates bidding behavior in repeated lottery contest: neural signatures from event-related potentials and electroencephalography oscillations - Hao, Su; Jiali, Pan; Xiaomin, Zhang; Xiaoqin, Wang; Lina, Lu; Xin, Qing; Qin, Liu (Frontiers in Neuroscience, 2023)
A contest usually involves expenditures, termed “overbidding,” exceeding the theoretical Nash equilibrium. A considerable number of studies have shown that group identity can affect decision-making and competitive behavior, thus providing a new perspective on alleviating the overbidding problem. How group identity influences brain activity when competitors bid in different groups is not yet clear, however. Thus, we conducted an EEG study to explore brain activity differences caused by participants’ different bidding behaviors under in-group and out-group conditions. Behavioral results showed that individual expenditure was significantly lower when bidding with in-group opponents than with out-group opponents. Analyses of event-related potentials (ERP) and event-related oscillations (ERO) revealed that compared to in-group conditions, greater N2 amplitudes, P3 amplitudes, and theta power were found under out-group conditions. To extend previous studies, we performed supplementary analysis to explore whether enhancement of group identity had effects on conflict alleviation. Behavioral results indicated that individual expenditure was significantly lower after enhancement group identity when bidding with in-group members, and EEG results showed more negative N2 amplitudes and larger theta power after enhancing group identity under in-group conditions. Collectively, these findings indicate that group identity modulated bidding behavior, and they provide insight into a mechanism to de-escalate in-group conflict by enhancing group identity.